Impact of polyethylene on soil physicochemical properties and characteristics of sweet potato growth and polyethylene absorption. (September 2022) - Shi, Liang; Hou, Yanan; Chen, Zanming; Bu, Yuan; Zhang, Xiyang; Shen, Zhenguo; Chen, Yahua
Abstract: Microplastic (MP) pollution problem is severe in China. As the main component of mulch film, whether polyethylene (PE) poses a threat to the safe production of sweet potato is unknown. In this study, micron-sized original or weathered PE was simulated as the field film particles, and pot, hydroponic experiment were conducted to explore the effects of original and weathered MPs on physicochemical properties in soil, growth and phosphorus (P), potassium (K) absorption in sweet potato; P and K adsorption in liquid environment, and also the distribution of original MPs in sweet potato tissues respectively. The results showed that 5 μm original PE MPs significantly reduced pH (5.6–7.9%) and increased EC (6.0–12.1%) of soil compared to weathered PE MPs. In addition, original PE MPs can also significantly improved the biomass growth rates (5.9–19.0%) of sweet potato compared with weathered PE MPs by adsorbing more Olsen-P and Olsen-K in soil, and increasing K concentration in stems compared with control (17.1–55.4%). Although there was no significant difference between original and weathered PE MPs on the degree of membrane lipid peroxidation in sweet potato leaves, the original PE MPs made sweet potato exhibit the stronger oxidative stress. The tissue distribution of PE MPs-fluorescent spheres were only observed in cortical tissues of roots and stems. Results from our study suggest that sweet potato were not significantly affected by a short term exposure to single PE MPs. Graphical abstract: Image 1 Highlights: PE MPs were investigated in sweet potato using fluorescence and cryo-scanning microscope. Original PE significantly reduced pH and increased EC of soil compared to weathered PE. Original PE has a strong adsorption effect on K, P in soil and favored growth. Fluorescent PE spheres were mainly found in cortical tissues of roots and stems.